2018
DOI: 10.1002/cam4.1423
|View full text |Cite
|
Sign up to set email alerts
|

Intake of bean fiber, beans, and grains and reduced risk of hormone receptor‐negative breast cancer: the San Francisco Bay Area Breast Cancer Study

Abstract: High dietary fiber intake has been associated with reduced breast cancer risk, but few studies considered tumor subtypes defined by estrogen receptor (ER) and progesterone receptor (PR) status or included racial/ethnic minority populations who vary in their fiber intake. We analyzed food frequency data from a population‐based case–control study, including 2135 breast cancer cases (1070 Hispanics, 493 African Americans, and 572 non‐Hispanic Whites (NHWs)) and 2571 controls (1391 Hispanics, 557 African Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 69 publications
3
24
0
1
Order By: Relevance
“…Breast cancer risk was reduced with the consumption of bean fiber ( p trend = 0.01), total beans ( p trend = 0.03), or total grains ( p trend = 0.05). Inverse associations were strongest for ER − /PR − breast cancer [ 170 ]. Meta-analysis of He et al [ 171 ] indicated a borderline inverse association between pre-diagnostic intake of fruit and overall survival of breast cancer, whereas intake of vegetables was not associated with survival.…”
Section: Epidemiological and Clinical Breast Cancer Studiesmentioning
confidence: 99%
“…Breast cancer risk was reduced with the consumption of bean fiber ( p trend = 0.01), total beans ( p trend = 0.03), or total grains ( p trend = 0.05). Inverse associations were strongest for ER − /PR − breast cancer [ 170 ]. Meta-analysis of He et al [ 171 ] indicated a borderline inverse association between pre-diagnostic intake of fruit and overall survival of breast cancer, whereas intake of vegetables was not associated with survival.…”
Section: Epidemiological and Clinical Breast Cancer Studiesmentioning
confidence: 99%
“…This approach has gained considerable attention because, in contrast to genetic alterations, epigenetic modifications are reversible and able to affect early carcinogenesis. Several clinical epidemiological studies and meta-analyses have demonstrated that long-term and regular (several times a week) consumption of plant-based whole foods is associated with a reduction in BC risk [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they contain unique phytochemicals that complement those of fruits and vegetables when consumed together. 22 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, they contain unique phytochemicals that complement those of fruits and vegetables when consumed together. 22,24 Many of the products produced with whole grains have greater antioxidant capacity in relation to vegetables and fruits. In addition, they supply vitamin E, an intracellular antioxidant that they allow to maintain selenium in its reduced state avoiding carcinogens precursors; reduced selenium prevents malignancy of cells exposed to carcinogens.…”
Section: Epigenetics and Metabolomics In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation